The PERMA well-being model and music facilitation practice: Preliminary documentation for well-being through music provision in Australian schools - Lee, J.; Krause, Amanda; Davidson, J. (SAGE Publications, 2017)
The aim of this study was to consider how we can invest in music-making to promote well-being in school contexts. Web-based data collection was conducted where researchers identified 17 case studies that describe successful music programs in schools in Australia. The researchers aligned content from these case studies into the five categories of the PERMA well-being model: Positive emotions, Engagement, Relationships, Meaning, and Accomplishment, in order to understand how each well-being element was realised through the music programs. The results indicate that the element of the PERMA well-being model that relates to relationships was described most often. Collaboration and partnership between students, teachers, and staff in schools, and local people in the community such as parents, local entrepreneurs, and musicians were repeatedly identified as a highly significant contributing factor in the success of the music program. The school leaders? roles in providing opportunities for students to experience musical participation and related activities (engagement) and valuing these experiences (meaning) were also crucial in the facilitation of the music programs. The findings of this study indicate that tailored music and relationship-centred music programs in schools not only increase skills and abilities of the students, but also improve the psychosocial well-being of the students and the community.